Tax Competition in Developed, Emerging and Developing Regions - Same Same but Different? - Mohammed Mardan; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper analyzes tax competition between countries which differ in their country-specific risk. We show that the outcome of asymmetric tax competition crucially depends on the ability of multinational firms to shift profits. With high costs of profit shifting, higher-risk countries set lower tax rates than lower-risk countries whereas the opposite is true if the costs of profit shifting are low. The results provide an explanation for the patterns observed in the corporate income tax policies across countries and regions differing in their level of development. Moreover, for intermediate costs of profit shifting, we show that also a country's absolute risk level affects countries' tax rate setting. These results carry important implication for the empirical tax competition literature.
Keywords: H25; O23; F23; 330; tax competition; country risk; developing countries; asymmetric countries